The performance of plant essential oils against lactic acid bacteria and adverse microorganisms in silage production - Chen, Lijuan; Li, Xi; Wang, Yili; Guo, Zelin; Wang, Guoming; Zhang, Yunhua (Frontiers in Plant Science, 2023)
Plant essential oils have played an important role in the field of antibiotic alternatives because of their efficient bacteriostatic and fungistatic activity. As plant essential oils are widely used, their activity to improve the quality of plant silage has also been explored. This review expounds on the active ingredients of essential oils, their bacteriostatic and fungistatic activity, and mechanisms, as well as discusses the application of plant essential oils in plant silage fermentation, to provide a reference for the development and application of plant essential oils as silage additives in plant silage fermentation feed.